2019
DOI: 10.1093/cercor/bhz098
|View full text |Cite
|
Sign up to set email alerts
|

Extracellular Pax6 Regulates Tangential Cajal–Retzius Cell Migration in the Developing Mouse Neocortex

Abstract: The embryonic mouse cortex displays a striking low caudo-medial and high rostro-lateral graded expression of the homeoprotein transcription factor Pax6, which presents both cell autonomous and direct noncell autonomous activities. Through the genetic induction of anti-Pax6 single-chain antibody secretion, we have analyzed Pax6 noncell autonomous activity on the migration of cortical hem-and septum-derived Cajal-Retzius (CR) neurons by live imaging of f lat mount developing cerebral cortices. Blocking extracell… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
14
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
3
2

Relationship

3
6

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 31 publications
1
14
0
Order By: Relevance
“…The capacity of a large number of homeoproteins to transfer is less of an open question despite the initial focus on only few homeoproteins. Non-cell-autonomous in vivo activity has been reported for EN1/2, PAX6, OTX2, KN1, several HOXs, and VAX1 (10,27,34,35,45,(65)(66)(67)(68)(69)(70), while all in vitro studies addressing the cellular mechanisms of transfer were done mainly with EN2. The hypothesis that most homeoproteins transfer in vivo is now supported by systematic assays involving 160 diverse homeoproteins in which intracellular transfer was confirmed for more than 150 homeoproteins both in HeLa cells and in mouse embryonic brain (13).…”
Section: Generalization Of Homeoprotein Intercellular Transfermentioning
confidence: 99%
“…The capacity of a large number of homeoproteins to transfer is less of an open question despite the initial focus on only few homeoproteins. Non-cell-autonomous in vivo activity has been reported for EN1/2, PAX6, OTX2, KN1, several HOXs, and VAX1 (10,27,34,35,45,(65)(66)(67)(68)(69)(70), while all in vitro studies addressing the cellular mechanisms of transfer were done mainly with EN2. The hypothesis that most homeoproteins transfer in vivo is now supported by systematic assays involving 160 diverse homeoproteins in which intracellular transfer was confirmed for more than 150 homeoproteins both in HeLa cells and in mouse embryonic brain (13).…”
Section: Generalization Of Homeoprotein Intercellular Transfermentioning
confidence: 99%
“…As an additional control, we also evaluated PV Cre ::scFvPAX6 tg/o mice. PAX6 homeoprotein is reported to also have noncell autonomous activities (Di Lullo et al, 2011;Kaddour et al, 2019), and these mice showed no visual acuity loss. These results demonstrate that neutralizing extracellular OTX2 in the retina leads to decreased visual acuity at P30, but the present results do not allow us to determine whether this persists at later ages.…”
Section: Resultsmentioning
confidence: 97%
“…Similar to findings in PARP1 KOs ( Hong et al, 2019 ), McLoughlin et al (2012) reported that Dicer depletion reduces cell proliferation and increases apoptosis in the E15.5 cortex. Additionally, PARP1 has a number of known transcription factor targets that have been shown to regulate CR progenitor cell development and migration, including Ascl1/Mash1, Pax6, and Cxcl12 ( Stoykova et al, 2003 ; Ju et al, 2004 ; Borrell and Marín, 2006 ; Dixit et al, 2011 , p. 1; Yoo et al, 2011 ; Marković et al, 2013 ; Tolić et al, 2019 ; Kaddour et al, 2020 ). Further studies will be necessary to test the links between PARP1, transcription factor activity, miRNAs, and CR cell generation in the embryonic brain.…”
Section: Discussionmentioning
confidence: 99%